Bos taurus and Bison bison conservative retrotransposon recombination products - Kosovsky, Gleb Yu.; Glazko, Galina V.; Skobel, Olga I. (Frontiers in Veterinary Science, 2025)
BackgroundWithout identifying and studying the genomic characteristics associated with domestication, managing farm animal genetic resources becomes overwhelmingly difficult. Accumulated data confirm that mobile genetic elements participate in the domestication process and, in particular, generate widely abundant microRNAs.MethodsThe recombination products were compared in silico between the long interspersed nuclear element (LINE) and the endogenous retrovirus (ERV), forming the LINE/ERV/LINE sequence, located in a closely linked conserved block of 12 genes, as well as the microRNAs formed by these recombination products in domesticated-wild pairs of mammals. For this comparison, the reference genomes of domesticated cattle (Bos taurus) and its closely related wild species counterpart, bison (Bison bison), were used.ResultsIt was found that the above-noted highly conserved recombination products (with more than 81.5% identity) were present in the corresponding block of 12 genes in bison. These recombination products served as sources of 51 microRNAs in bison and 129 microRNAs in cattle, including 50 microRNAs that were similar in both species. A total of 79 microRNAs were found only in cattle trinomial recombination products, with 98% belonging to the mir-30 family, including the cattle-specific bta-miR-30a-5p and bta-miR-30e-5p. The mir-30 family is closely associated with biological processes influencing the quantity and quality of agricultural products.ConclusionTrinomial retrotransposon recombination products were fixed in both the cattle genome and the genome of its closely related wild species, the bison. It was found that these products may be involved in the response to intensive artificial selection and the domestication process since interspecific differentiation of microRNAs is associated with regulatory networks that have a significant impact on the formation of economically important traits.